Device for the assessment of occupational exposure to time‐varying magnetic field due to movement in magnetic resonance environments. Issue 10 (1st May 2019) - Hartwig, V.; Ferrante Vero, L.F.; Virgili, G.; Landini, L.; Giovannetti, G.
Abstract : Also according to the recent Directive by the European Parliament and the Council of the European Union, there is a need for a simple but reliable device to measure exposure to the magnetic field (MF) of magnetic resonance (MR) workers, especially given the continuing development of scanner using a higher static MF. Here the authors describe a novel device for assessing personal exposure to the MF. The time recording system can measure the static MF value at which the operator is exposed to and the field gradients due to his/her movements in the MR environment. The device does not require any cable for data management and transmission and it is able to record the instantaneous and cumulative exposition dose. The device can be used in all MR environments, for clinical or industrial applications.